LoRaWAN: Solution for Monitoring Differential Pressure Room in Pharmaceutical Industry - Enriko , I Ketut Agung; Gustiyana , Fikri Nizar (International Journal of Membrane Science and Technology, 2023)
The air conditioning system is a process continuous air control of air temperature, air humidity, air cleanliness, air quality, speed indoor air, air distribution evenly throughout the room as well control the noise that can caused by the air conditioning equipment itself according to the needs and conditions wanted especially in drug factories. In This research we use IoT Technologi to provide system to monitoring Differential Pressure room in Pharmaceutical room based on LoRaWAN. LoRaWAN is one of the LPWAN technologies which also provides a wide range of coverage, low power, and low cost in the implementation. The result of this study are very satisfactory, it can be seen that the results of the LoRaWAN implementation are very good with an indication of the worst RSSI value of -91 dbm and an error value on the Differential Pressure sensor device of 0.65 Pascal.